Investigating Human Resource Management And Leadership In Enhancing Community Performance Of Health Centers: A Cross-Sectoral Survey - Achmad Masfi; Qory Tifani Rahmatika; Muhammad Putra Ramadhan; Nurma Nuafiani; Nurul Evi; Neni Fidya Santi; Yhenti Widjayanti; Eri Yanuar ABS (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2026)
Introduction: The main problem in health services is the drastic decrease in the performance of the Health Center. The performance of the Puskesmas represents the achievement of its organizational goals. This study aims to analyze how human resource management and leadership impact the performance of Puskesmas. Methods: We designed the design of this study using a cross-sectional sample of 231 nurses. This sample was obtained using cluster sampling with the total population of all nurses spread across 21 health centers. Data collection used a questionnaire instrument with a review of the McKinsey 7s Framework for independent variable instruments, namely leadership and Human Resource Management, while for the performance instrument of Puskesmas as a dependent variable, using Indonesian government standards. Statistical analysis in this study used the Spearman rating test.Results: Of the 213 nurses analyzed, 111 (52%) received a good leadership rating, while 4 (1.9%) were rated as lacking. For human resource management, 138 nurses (64.8%) fell into the sufficient category, and 2 (0.9%) into the less category. Regarding health center performance, 110 (51.5%) nurses evaluated it as good, with the remainder categorized as less. The Spearman rating test revealed statistically significant associations between leadership, human resource management, and health center performance.Conclusion: This study provides strong evidence that leadership and human resource management significantly influence the performance of Puskesmas in Sampang Regency. Strengthening these factors may be key to improving health center outcomes.Â Keyword: Leadership, human resource management, indonesian society, labor, government, nursesÂ